Investigation into Macro- and Microcrack Propagation Mechanism of Red Sandstone under Different Confining Pressures Using 3D Numerical Simulation and CT Verification - Wen Zhang; Yan-yu Chen; Jin-ping Guo; Sai-sai Wu; Cheng-yuan Yan (Geofluids)
The growth and evolvement features of crack are of great significance to study the failure mechanism of rock mass and valuate the stability of the cavity. In this study, in order to obtain the mechanics parameters and external macroscopic crack propagation characteristics of red sandstone, triaxial compression tests were carried out. Based on the experimental results, a numerical model was established through the reasonable parameter calibration by the PFC3D software. The internal and external crack propagation processes of red sandstone under triaxial compression were simulated. Moreover, to verify the simulation results, the CT scanning and three-dimensional reconstruction technologies were used to observe the internal crack state of the specimens. The results showed that the internal crack failures occurred first at the end of the rock specimen. Then, the microcracks continued to accumulate and expand under the combined action of axial stress and confining pressure. The accumulated microcracks finally converged to form a macroscopic oblique shear failure. Based on the homogenizing treatment and reasonable parameter calibration, the internal and external crack expansion and evolution processes of the rock were simulated by the PFC3D model and the simulation results are consistent with the results obtained from the triaxial compression test and the CT scanning. The macro- and microfailure mode of crack propagation of the specimen deepens the understanding of rock failure mechanism. The PFC3D homogenization simulation method provides a new feasible method to study the macro- and microfailure mode of internal and external crack propagation of rock under compression.